comunicación interna en los diferentes departamentos del Gobierno Autónomo Descentralizado del cantón Montalvo - Peña Quinto, Felix Geovanny (2018)
The case study was carried out in the Autonomous Decentralized Government of the Montalvo Canton with the purpose of knowing the problems that this institution is going through and therefore taking measures that can solve them, the issue is the internal communication in the different departments of the Cantonal Montalvo GAD.